Dampak Konsep Diri dan Identifikasi Komunal terhadap Loyalitas Merek GoPay pada Muslimah di Surakarta: Peran Mediasi Engagement dan Self-Brand Connection (Jurnal Simki Economic, 2025)
This study aims to examine the direct effect of self-concept involvement and communal focus in creating and increasing brand loyalty in the GoPay transaction service company by testing the mediating influence of CEB and SBC. This study uses self-congruity theory to provide a psychological perspective for SBC. Quantitative approach using surveys to predict the relationship between variables. Participants in this study were selected using purposive sampling technique based on certain criteria such as Muslim women in Surakarta and using GoPay services with a total of 200 respondents. Data were analyzed using Structural Equation Modeling (SEM) and SmartPLS. The main findings show that self-concept generates loyalty through the mediation of SBC and CEB. In addition, the communal focus variable mediated by SBC and CEB also has a significant effect on loyalty. Since self-concept and communal focus are significantly related to loyalty, it is important for brands to conduct market research and support a brand community.